Relational solidarity and COVID-19: an ethical approach to disrupt the global health disparity pathway. (1st January 2021) - Ho, Anita; Dascalu, Iulia
ABSTRACT: While the effects of COVID-19 are being felt globally, the pandemic disproportionately affects lower- and middle-income countries (LMICs) by exacerbating existing global health disparities. In this article, we illustrate how intersecting upstream social determinants of global health form a disparity pathway that compromises LMICs' ability to respond to the pandemic. We consider pre-existing disease burden and baseline susceptibility, limited disease prevention resources, and unequal access to basic and specialized health care, essential drugs, and clinical trials. Recognizing that ongoing and underlying disparity issues will require long-term correction efforts, this pathway approach is nonetheless helpful to inform ethical responses to this global pandemic. It can facilitate international cooperation during the pandemic to reduce the disparate burdens among different regions without imposing significant burden on any particular contributor. The pathway approach allows international stakeholders in various social positions to respond to different components of the pathway based on their respective strengths and resources to help break the cycle of global health inequity. Guided by the ethical principles of relational and pragmatic solidarity, we argue for a coordinated global division of labor such that different stakeholders can collaborate to foster equitable healthcare access during this pandemic.